Meneropong pelaku kawin misyar di Surabaya dari sudut dramaturgi Erving Goffman - Nasiri Nasiri (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
The research is designed qualitatively, focusing on the aspects that become the background (motives) tothe decision of choosing misyarmarriage among career women in Surabaya. Reseach results show: First,the model of misyar marriage is to give a solution to busy women who have no time to think aboutmarriage. In the midst of their busy life, these women can enjoy marriage, because in this marriagehusband and wife do not have to live in the same house. Therefore, the wife can do her normal activitieslike before she is married, so can the husband. Secondly, it can be inferred from the practice of misyarmarrigein Surabaya in the perpective of Dramaturgy theory that the average actors of misyarmarriage are middleto-upper class women, both n terms of education economy. They are smart and active in simultaneouslyplaying two roles. On the one hand, ther are just single women at home, but married womenwhen staying in a hotel or motel. However on the other hand, in a quiet place or in bed, they are marriedwomen, but when they do their activities or even mingle with single women, they will admit to be singleas well.